Central America Social Expenditures and Institutional Review : Costa Rica - World Bank (World Bank, Washington, DC, 2016)
The evolution of Costa Rica’s social sectors over the past decade has been dichotomous. On the one hand, economic growth has remained relatively high, however poverty and inequality have not declined (moreover, they have increased), and persistent employment challenges remain. On the other hand, the country has continued experiences advances in many social indicators, such as pre-primary and tertiary enrollment rates, access to improved sanitation, and labor force participation, though not in others (secondary school completion, immunizations, employment). Higher economic growth and (to a lesser extent) revenues seem to have allowed a substantial increase in public social spending. Looking forward, the key challenges Costa Rica faces are related to continuing improving the quality and efficiency in the social sectors, while improving targeting to serve the most in need, in a tight and severe fiscal context. To expand coverage of excluded population, priority will have to be given to reallocations and improvements within the spending envelope for the social sectors to maximize impact. With a fiscal deficit of more than 6 percent of GDP, further expanding public social spending is no longer an option and budget cuts are looming. Improvements in public spending management and budget execution, including the need of institutional reform to consolidate programs and improve coordination among executing agencies is equally important. In a country that has long been the champion in expanding universal welfare state, sustainability concerns will imply that hard fiscal decisions would need to be made to increase the social returns of budget allocation.